Progress in Basic Research and Clinical Strategies for Cementum Regeneration - Xiaoxue Zhu; Dandan Xiang; Yiding Huo; Xiaotao He; Faming Chen; Beimin Tian; Xuan Li (International Dental Journal)
Periodontitis is a chronic inflammatory disease that inflicts damage to periodontal tissues, leading to loss of teeth, and affects systemic health. Traditional treatments can delay inflammation, whereas regeneration of the periodontal complex (periodontal ligament, cementum, and alveolar bone) can better restore periodontal tissue function. In recent years, the regeneration of alveolar bone and the periodontal ligament has been widely reviewed although cementum has received less attention. As an avascular mineralised structure around the tooth, cementum can anchor periodontal ligament fibres to the root surface, thereby connecting teeth to alveolar bone. The supporting and stabilizing effects of cementum make its regeneration vital for restoring the functionality of the periodontal tissues. In this review, we discuss advancements in basic and clinical research appertaining to cementum regeneration. We describe the molecular mechanisms that contribute to cementum regeneration thereby providing a foundation for further basic research. Finally we summarise the clinical strategies employed for cementum regeneration, including regenerative surgery and utilisation of growth factors and stem cells.